Sosialisasi Manajemen Keuangan Rumah Tangga Islami Sebagai Upaya Peningkatan Literasi Keuangan Masyarakat Desa Pangirkiran Dolok - Erwin Hamonangan Pane```; Ismail Nasution; Irma Sari Daulay; Era Mutiah; Ahmad Fadhlan Gulo; Hotma Yudha Ananda Daulay; Rahma Nilam Cahya Hasibuban; Sefri Maryam Hasibuan (Jurnal Transformasi Pendidikan Indonesia, 2025)
The problem of low financial literacy in rural communities often results in unbalanced consumption patterns, lack of financial planning, and low awareness of saving and investing based on sharia principles. The Field Work Lecture (KKL) activity in the form of Community Service (PKM) in Pangirkiran Dolok Village was focused on the socialization of Islamic household financial management as an effort to improve community financial literacy. The purpose of this activity was to provide understanding of sharia-compliant financial management concepts, enhance community skills in financial planning and household bookkeeping, and encourage the growth of a saving culture and halal investment. The implementation methods included interactive lectures, group discussions, and practical simulations of family financial recording. The results showed a significant increase in community understanding and skills in financial management, as reflected in more directed and Islamic-oriented financial behavior. The impact was the emergence of collective community awareness of the importance of sharia financial management as the foundation for family welfare and village economic development.